In vivo quantification of lymph viscosity and pressure in lymphatic vessels and draining lymph nodes of arthritic joints in mice. (12th February 2014) - Bouta, Echoe M.; Wood, Ronald W.; Brown, Edward B.; Rahimi, Homaira; Ritchlin, Christopher T.; Schwarz, Edward M.
<x xml:space="preserve">Abstract</x> Key points Previously, it was found that the popliteal lymph node (PLN) enlarges during the pre‐arthritic 'expanding' phase, and then 'collapses' with adjacent knee flare and is associated with the loss of the intrinsic lymphatic pulse. However, the mechanisms responsible are unknown and we therefore developed in vivo methods to measure lymph viscosity, lymphatic pumping pressure (LPP) in the lymphatic vessels afferent to the PLN, and lymph node pressure (LNP). Multiphoton fluorescence recovery after photobleaching (MP‐FRAP) was used to calculate lymph viscosity and speed; no difference was found among mice with wild‐type (WT), expanding or collapsed PLN in lymph viscosity, but lymph speed was found to be decreased in mice with collapsed PLN compared to WT and expanding PLN mice. LPP was measured indirectly by slowly releasing a pressurized cuff occluding ICG fluorescent dye; we found that mice with expanding PLN exhibit a higher LPP compared to WT and mice with collapsed PLN show an extremely low LPP. Direct measurement of LNP demonstrated a decrease in expanding PLN versus WT pressure, which dramatically increased in collapsed PLN. The decrease in lymphatic flow and loss of LPP during PLN collapse are consistent with decreased drainage from the joint during arthritic flare, and validate these biomarkers of rheumatoid arthritis progression and possibly other chronic inflammatory conditions Abstract Rheumatoid arthritis (RA) is a chronic inflammatory joint disease with episodic flares. In TNF‐Tg mice, a model of inflammatory–erosive arthritis, the popliteal lymph node (PLN) enlarges during the pre‐arthritic 'expanding' phase, and then 'collapses' with adjacent knee flare associated with the loss of the intrinsic lymphatic pulse. As the mechanisms responsible are unknown, we developed in vivo methods to quantify lymph viscosity and pressure in mice with wild‐type (WT), expanding and collapsed PLN. While no differences in viscosity were detected via multiphoton fluorescence recovery after photobleaching (MP‐FRAP) of injected FITC‐BSA, a 32.6% decrease in lymph speed was observed in vessels afferent to collapsed PLN (P < 0.05). Direct measurement of intra‐lymph node pressure (LNP) demonstrated a decrease in expanding PLN versus WT pressure (3.41 ± 0.43 vs. 6.86 ± 0.56 cmH2O; P < 0.01), which dramatically increased to 9.92 ± 1.79 cmH2O in collapsed PLN. Lymphatic pumping pressure (LPP), measured indirectly by slowly releasing a pressurized cuff occluding indocyanine green (ICG), demonstrated an increase in vessels afferent to expanding PLN versus WT (18.76 ± 2.34 vs. 11.04 ± 1.47 cmH2O; P < 0.01), which dropped to 2.61 ± 0.72 cmH2O (P < 0.001) after PLN collapse. Herein, we document the first in vivo measurements of murine lymph viscosity and lymphatic pressure, and provide evidence to support the hypothesis that lymphangiogenesis and lymphatic transport are compensatory mechanisms to prevent synovitis via increased drainage of inflamed joints. Furthermore, the decrease in lymphatic flow and loss of LPP during PLN collapse are consistent with decreased drainage from the joint during arthritic flare, and validate these biomarkers of RA progression and possibly other chronic inflammatory conditions.